Additive manufacturing in medical sciences: past, present and the future - Rathore, Lakshya P.; Verma, Naina (International Journal of Research in Orthopaedics, 2018)
Additive manufacturing (AM) is a novel technique that despite having been around for more than 35 years, has been underutilized. Its great advantage lies in the basic fact that it is incredibly customizable. Since its use was recognized in various fields of medicine like orthopaedics, otorhinolaryngology, ophthalmology etc, it has proved to be one of the most promising developments in most of them. Customizable orthotics, prosthetics and patient specific implants and tracheal splints are few of its advantages. And in the future too, the combination of tissue engineering with AM is believed to produce an immense change in biological tissue replacement.